(untitled) - Talbott, Hudson (Morrow, 1999)
Lancelot is welcomed into the court of King Arthur as a valiant fighter and later rescues Queen Guinevere, fights the tournament at Astolat, and pursues other adventures.
K-6.
Keywords: Folklore; Folklore; Knights and knighthood; Legends; Arthurian romances; England; Lancelot (Legendary character)